Superelastic load cycling of Gum Metal. (15th April 2015) - Vorontsov, V.A.; Jones, N.G.; Rahman, K.M.; Dye, D.
Abstract: The superelastic beta titanium alloy, Gum Metal, has been found to accumulate plastic strain during tensile load cycling in the superelastic regime. This is evident from the positive drift of the macroscopic stress vs. strain hysteresis curve parallel to the strain axis and the change in its geometry subsequent to every load–unload cycle. In addition, there is a progressive reduction in the hysteresis loop width and in the stress at which the superelastic transition occurs. In situ synchrotron X-ray diffraction has shown that the lattice strain exhibited the same behaviour as that observed in macroscopic measurements and identified further evidence of plastic strain accumulation. The mechanisms responsible for the observed behaviour have been evaluated using transmission electron microscopy, which revealed a range of different defects that formed during load cycling. The formation of these defects is consistent with the classical mathematical theory for the bcc to orthorhombic martensitic transformation. It is the accumulation of these defects over time that alters its superelastic behaviour.